Answer:
The simplest form is 1/r^7 + 1/s^12
Step-by-step explanation:
The given expression is r^-7+s^-12.
Notice that the exponents of both the base are negative
So, we will apply the rule which is:
a^-b = 1/a^b
Which means that to change the exponent into positive we will write it as a fraction:
r^-7+s^-12.
= 1/r^7 + 1/s^12..
Therefore the simplest form is 1/r^7 + 1/s^12....
Answer:8
Step-by-step explanation:
You find the average which is adding them all together then dividing by how many numbers you added.
Answer: 2
Step-by-step explanation:
Answer:
Step-by-step explanation:
The triangle in the given problem is a right triangle, as the tower forms a right angle with the ground. This means that one can use the right angle trigonometric ratios to solve this problem. The right angle trigonometric ratios are as follows;
Please note that the names () and () are subjective and change depending on the angle one uses in the ratio. However the name () refers to the side opposite the right angle, and thus it doesn't change depending on the reference angle.
In this problem, one is given an angle with the measure of (35) degrees, and the length of the side adjacent to this angle. One is asked to find the length of the side opposite the (35) degree angle. To achieve this, one can use the tangent () ratio.
Substitute,
Inverse operations,
Simplify,
Answer: 21/44
Step-by-step explanation:
Given that:
Bag contains :
6 red apples
6 yellow apples
Number of samples drawn = 3
Probability that sample contains more red than yellow :
Then from the three samples, red = 2 and yellow = 1 or red for all 3
Prob of RRR = (6/12)(5/11)(4/10)= 120 / 1320
Prob RRY = (6/12)(5/11)(6/10)= 150/1320
Prob RYR is (6/12)(6/11)(5/10)= 180/1320
Prob YRR is (6/12)(6/11)(5/10)=180/1320
120/1320 + 150/1320 + 180/1320 +. 180/1320 = 630/1320 =126/264 = 42/88 = 21/44